Tetramethylpyrazine alleviates cerebral ischemia-reperfusion injury via NRF2/HO-1/GPX4-mediated ferroptosis inhibition - Hengpei Gong; Yinjun Lu; Lingfeng Wang; Xueyuan Gong; Jingfang Zhao; Zhenxin Li (Tissue and Cell, 2027)

Biphasic multiplex PCR based on bead array for high-throughput and sensitive authentication of meat products - Lingfeng Yan; Rong Cao; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Food Control, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Multi-objective optimization of ship resistance and seakeeping using an improved Voronoi-based parallel sequential sampling method - Dongqin Li; Yu Zhang; Yanqing Yin; Wenwen Chen; Bohan Wang; Zishuai Wang; Lingfeng Lu (Ocean Engineering, 2026)

HMGB1 blockade attenuates cardiac injury induced by radiotherapy combined with PD-1 inhibitor while maintaining the anti-tumor efficacy - Yao Liu; Lingfeng Liu; Bibo Wu; Jing Zhang; Chaofen Zhao; Bing Lu; Yinxiang Hu; Weiwei Ouyang; Zhenneng Guo; Rong Hu; Shengfa Su (Apoptosis, 2026)

Clinical efficacy and mechanistic study of intrauterine administration of E bing angong Ye for the treatment of endometritis in sows - Yi-Meng Fan; Xinyi Zhou; Lu Wang; Xiyu Wen; Xueyan Wang; Lingfeng Peng; Luyao Wang; Zhihui Hao (Theriogenology, 2026)

Development of a high-throughput sensitive SB-PCR assay for rapid detection of laboratory-escaped antibiotic resistance genes - Lingfeng Yan; Shengnan Liu; Rong Cao; Azadeh Nilghaz; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Journal of Environmental Chemical Engineering, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Fibre–emulsifier interactions shape the lipid digestion behaviour of high internal phase emulsions - Yifeng Lu; Lingfeng Wu; Aprilia Nur Khasanah; Maarten Schutyser; Lu Zhang; Karin Schroën; Meinou Corstens (Food Hydrocolloids, 2026)

Multi-omics and neurophysiological insights into flavor enhancement of low-salt shrimp paste fermented by Bacillus velezensis BV-T11 - Kuan Lu; Haoen Li; Lingfeng Ji; Yuhan Zheng; Wancui Xie (Chemical Engineering Journal, 2026)

The sea level rise of the 8.2 ka event simulated by the iCESM1.3 - Lingfeng Wan; Zhengyu Liu; Chengfei He; Chenyu Zhu; Shaoqing Zhang; Jiuyou Lu; Zhaowei Jing (Climate Dynamics, 2026)

Parallel cooperative path following control for multiple cyber-physical MASSs based on DN-ESO - Lingfeng Li; Lu Liu; Bing Han; Bing Wu; Zhouhua Peng (Ocean Engineering, 2026)

Antarctic circumpolar current evolution and its relation to southern hemisphere westerly winds during the holocene - Lingfeng Wan; Dapeng Li; Chenyu Zhu; Zhengyu Liu; Shaoqing Zhang; Xiaopei Lin; Jiuyou Lu (Climate Dynamics, 2025)

Near-complete assembly and comprehensive annotation of the wheat Chinese Spring genome - Zijian Wang; Lingfeng Miao; Kaiwen Tan; Weilong Guo; Beibei Xin; Rudi Appels; Jizeng Jia; Jinsheng Lai; Fei Lu; Zhongfu Ni; Xiangdong Fu; Qixin Sun; et al. (Molecular Plant, 2025)

A New Record and Three Redescriptions of Rissoinidae from China’s Hainan Island, with the First Presentation of Two Mitochondrial Genomes in the Family Rissoinidae - Lu Qi; Lingfeng Kong; Zhenhua Ma (Fishes, 2025)
The family Rissoinidae represents a significant component of microgastropod diversity, with a global distribution spanning temperate to tropical zones and encompassing over 300 recorded species. Hainan Island, the largest island in the South China Sea, harbors a rich diversity of mollusks, but the family Rissoinidae remains poorly studied in this region. Here, we report three rissoinid species and one newly recorded species from Hainan Island, providing detailed taxonomic descriptions supported by SEM imaging. For the first time, we provide the mitochondrial genomes of Rissoina cardinalis and Phosinella seguenziana, analyzing their genome structure and nucleotide composition, thereby addressing the existing knowledge gap in Rissoinidae research. A phylogenetic tree of the family Rissoinidae was reconstructed using the COI gene, clarifying the intergeneric relationships within the family. Notably, the genus Rissoina is revealed as a non-monophyletic group, likely due to the limitations of single-gene analyses in providing adequate phylogenetic information.

The coupling of ultra-nano oxygenation and in-situ sediment remediation technology jointly promotes phosphorus enrichment and nitrogen removal - Lu Cao; Lingling Wan; Chunhui Xi; Zijun Zhou; Siyang Wang; Lingfeng Cao; Zhicheng Min; Xiankun Chen; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Journal of Water Process Engineering, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

Intelligent identification of carbonate components based on deep learning - Yuqing Dong; Chenlin Hu; Jonathan Atuquaye Quaye; Ning Lu; Lingfeng Zhao (Facies, 2025)

Response of nitrifiers to gradually increasing pH conditions in a membrane nitrification bioreactor: Microbial dynamics and alkali-resistant mechanism - Weican Shi; Zhaoming He; Jiahui Lu; Lingfeng Wang; Jianhua Guo; Shuang Qiu; Shijian Ge (Water Research, 2025)

Optimal balance of organic detritus and feed for fish growth and water quality improvement through regulating nutrients cycling - Lu Cao; Lingling Wan; Lingfeng Cao; Zhicheng Min; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Environmental Research, 2024)

Diversification in birds is promoted by plant diversity, topographic heterogeneity and stable paleoclimate - Xinyu Wang; Lu Miao; Xiongwei Huang; Lingfeng Mao; Tianlong Cai; Jens‐Christian Svenning; Gang Feng (Journal of Biogeography, 2024)
Aims Long‐term climate stability, contemporary climate and environmental heterogeneity have been linked to bird diversity patterns through their direct impacts on diversification rate, as well as through their indirect effects on plant species richness, which could also directly and indirectly affect bird diversity. This study aimed to quantitatively assess whether these potential drivers could indirectly affect bird species richness through their direct effects on the diversification rate in birds in eastern Asia. Location Mainland China. Taxon Birds. Methods Using the distribution data of 1127 bird species across 320 prefecture cities in China and a phylogenetic tree of these bird species, we analysed the distribution patterns of bird species richness and diversification rate of all birds, passerine birds and non‐passerine birds, respectively. We also investigated their relationships with long‐term climate stability, contemporary climate, elevation range and plant diversity using ordinary least squares regression model and simultaneous autoregressive model. In addition, structural equation model was used to analyse whether these drivers could indirectly affect bird species richness through their direct effects on bird diversification rate. Results The results showed that bird species richness and diversification rate were highest in southwestern China. Additionally, diversification rate for passerine birds was higher than non‐passerine birds and all birds. Regression analyses revealed that plant species richness was the variable most associated with bird species richness and diversification rate across the three groups. Notably, results from structural equation model indicated that plant species richness, elevation range and glacial–interglacial climate change can indirectly influence bird species richness by directly affecting diversification rates. Main Conclusions These findings emphasize the importance of considering diversification rate when understanding the geographic distribution patterns of bird diversity. The direct and indirect effects of plant species richness, elevation range and glacial–interglacial climate change on bird diversity highlight the crucial role of mountain regions with higher plant diversity and stable paleoclimate in forming and maintaining biodiversity.

Urbanization significantly increases greenhouse gas emissions from a subtropical headwater stream in Southeast China - Mutan Dai; Yuanhui Xu; Yegenberdy Genjebay; Lingfeng Lu; Chuan Wang; Hao Yang; Changchun Huang; Tao Huang (Science of The Total Environment, 2024)

Increased microgastropoda sampling give new insights into the phylogenetic relationships of Littorinoidea (Littorinimorpha) - Lu Qi; Ning Zhang; Biyang Xu; Qinzeng Xu; Xiao Han; Lingfeng Kong; Qi Li (Molecular Phylogenetics and Evolution, 2024)

A multiplex method for the detection of food microorganisms based on suspension microarrays combined with recombinase-aided amplification - Wentao Zeng; Xihao Fan; Azadeh Nilghaz; Gengfen Zhao; Lingfeng Yan; Zhuoxuan Lu; Liming Zhang (Food Bioscience, 2024)

A new multiscale Cosserat model for size effect simulation in granular media - Lingfeng Guo; Xiaolong Li; Lu Ren; Yuanming Lai; Junsheng Chen; Lunyang Zhao (Computers and Geotechnics, 2024)

Wide-bandgap donor polymers from organic photovoltaics as dopant-free hole transport layers for perovskite solar cells - Hongtao Lai; Xin Yang; Liujiang Zhang; Leyu Bi; Binqiang Tian; Huanhuan Wang; Xingyu Gao; Lingfeng Lu; Bin Kan; Xiaofei Ji; Qiang Fu (Chemical Engineering Journal, 2024)

Physiological and transcriptomic analysis revealed that the accumulation of reactive oxygen species caused the low temperature sensitivity of Liriodendron × sinoamericanum - Ye Lu; Lingfeng Hu; Long Yu; Shuang Liang; Haoxian Qu; Mingqi Wang; Zhaodong Hao; Liming Yang; Jisen Shi; Jinhui Chen (Plant Science, 2024)

Seipin Deficiency Leads to Energy Dyshomeostasis via Inducing Hypothalamic Neuroinflammation and Aberrant Expression of Neuropeptides - Wenli Cui; Hong Chen; Lingfeng Lei; Wenru Wang; Kah-Leong Lim; Chengwu Zhang; Li Lu (NeuroMolecular Medicine, 2024)

Differences in the activities of six soil enzymes in response to cadmium contamination of paddy soils in high geological background areas - Juan Liu; Xinyang Li; Qilin Zhu; Jiawen Zhou; Lingfeng Shi; Weihong Lu; Li Bao; Lei Meng; Longhua Wu; Naiming Zhang; Peter Christie (Environmental Pollution, 2024)

Effects of cadmium exposure during pregnancy on genome-wide DNA methylation and the CREB/CREM pathway in the testes of male offspring rats - Xiushuai Du; Jianlin Zhu; Xueming Xu; Zhilan Lu; Xiaoqin Li; Yuchen Li; Lingfeng Luo; Wenchang Zhang; Jin Liu (Chemosphere, 2024)

Taxonomy and distribution of three species of Barleeia (Mollusca, Gastropoda, Littorinimorpha, Barleeiidae) in the intertidal zone off the coast of China, with description of a new species, Barleeia qilu Han, Qi & Kong, n. sp. - Xiao Han; Biyang Xu; Lu Qi; Shiyuan Liu; Lingfeng Kong (Molluscan Research, 2024)

Revealing the specificity of map method to predict the performance of a combined cooling and power cycle under operating conditions - Yu Yao; Lingfeng Shi; Jintao He; Xiaocun Sun; Bowen Lu; Yonghao Zhang; Hua Tian; Xuan Wang; Gequn Shu (Journal of Cleaner Production, 2023)

Improved phylogenetic resolution within Neritidae (Gastropoda, Nertimorpha) with implications for the evolution of shell traits and habitat - Lu Qi; Biyang Xu; Lingfeng Kong; Qi Li (Zoologica Scripta, 2023)
Neritidae is a species‐rich family with substantial interspecific morphological and ecological diversities. The current classification of Neritidae is controversial, particularly regarding the taxonomic position of Smaragdiinae. Although several molecular phylogenetic studies have attempted to clarify the phylogeny of Neritidae, the internal evolutionary relationships have not been completely resolved due to limited sampling. We recently sequenced eight mitochondrial genomes of Neritidae, reassembled five previously published transcriptome data, and reconstructed a comprehensive phylogeny for Neritidae with mitochondrial genome (13 protein‐coding genes) datasets of up to 23 species. Phylogenetic analyses using maximum likelihood and Bayesian inference indicated that the Neritidae were divided into two monophyletic groups, Neritinae and Neritininae, with strong support. A representative of Smaragdiinae, Smaragdia rangiana , was found to nest within Neritininae. Within Neritininae, the monophyly of Clithon and Neritina has not been recovered. Ancestral state reconstruction indicated that the most recent common ancestor of the Neritidae was a smooth shell. Our results imply at least two transitions from marine to brackish habitats within Neritidae.

Correction: Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Effect of Angiogenesis in Bone Tissue Engineering - Jianhao Huang; Qixiu Han; Meng Cai; Jie Zhu; Lan Li; Lingfeng Yu; Zhen Wang; Gentao Fan; Yan Zhu; Jingwei Lu; Guangxin Zhou (Annals of Biomedical Engineering, 2022)

Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Mitogenomics reveals phylogenetic relationships of Patellogastropoda (Mollusca, Gastropoda) and dynamic gene rearrangements - Tao Xu; Lu Qi; Lingfeng Kong; Qi Li (Zoologica Scripta, 2022)
Patellogastropoda has been recognized as the most ‘primitive’ group of living Gastropoda and plays important role in littoral marine ecosystems. Both morphological and molecular works have attempted to resolve the phylogenetic framework of Patellogastropoda, but evolutionary relationships among major lineages remain controversial. In addition, a few mitogenomes sequenced of Patellogastropoda exhibit extensive rearrangements; however, it was unclear that which one can represent the ancestral gene arrangement. In this regard, we sequenced 10 new mitochondrial genomes and analysed them with previously published nine mitogenomes and six transcriptomic data which represent six families of Patellogastropoda. A well‐supported phylogeny was reconstructed based on the amino acid sequences of 13 protein‐coding genes, recovered Lottioidea as non‐monophyletic with two well‐supported lineages. Comprehensive taxon sampling in Lottiidae allows us to recover Lottia digitalis sister to Lottia cassis . Comparing gene order among families, genera and species showed that Nacellidae has a conserved gene arrangement which is similar to that of hypothetical ancestral Gastropoda, whereas Lottiidae exhibits extensive rearrangements even without considering the changes of tRNA genes. A chronogram dating mayor cladogenetic events within the group was also reconstructed. Our results provide new insights into the phylogenetic relationships of Patellogastropoda and detect dramatic gene rearrangements within the group.

Study on bioleaching of heavy metals and resource potential from tannery yard sludge - Hang Liu; Kaizhi Yang; Lingfeng Luo; Qian Lu; Yonggui Wu; Meiyan Lan; Youfa Luo; Wan Liang (Environmental Science and Pollution Research, 2021)

QSAR modeling and in silico design of small-molecule inhibitors targeting the interaction between E3 ligase VHL and HIF-1 $$α $$ α - Jing Pan; Yanmin Zhang; Ting Ran; Anyang Xu; Xin Qiao; Lingfeng Yin; Weineng Zhou; Lu Zhu; Junnan Zhao; Tao Lu; Yadong Chen; Yulei Jiang (Molecular Diversity, 2017)

Chitosan scaffolds induce human dental pulp stem cells to neural differentiation: potential roles for spinal cord injury therapy - Jinlong Zhang; Xiaohui Lu; Guijuan Feng; Zhifeng Gu; Yuyu Sun; Guofeng Bao; Guanhua Xu; Yuanzhou Lu; Jiajia Chen; Lingfeng Xu; Xingmei Feng; Zhiming Cui (Cell and Tissue Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Molecular characterization and multiple infections of rotavirus, norovirus, sapovirus, astrovirus and adenovirus in outpatients with sporadic gastroenteritis in Shanghai, China, 2010–2011 - Lijuan Lu; Ran Jia; Huaqing Zhong; Menghua Xu; Liyun Su; Lingfeng Cao; Zuoquan Dong; Niuniu Dong; Jin Xu (Archives of Virology, 2015)

Weak coupling between heterotrophic nanoflagellates and bacteria in the Yellow Sea Cold Water Mass area - Shiquan Lin; Lingfeng Huang; Jiachang Lu (Acta Oceanologica Sinica, 2014)

Molecular epidemiology of human calicivirus infections in children with acute diarrhea in Shanghai: a retrospective comparison between inpatients and outpatients treated between 2006 and 2011 - Lijuan Lu; Huaqing Zhong; Menghua Xu; Liyun Su; Lingfeng Cao; Niuniu Dong; Jin Xu (Archives of Virology, 2014)